IMPLEMENTASI MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) PADA APLIKASI MEDIA PEMBELAJARAN BUDAYA JAWA BARAT DI KOMPEPAR GIRI HARJA JELEKONG - Ilma, Ilma Amalia Jaza; Darsiti (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Indonesia has a diverse culture. Kompepar Giri Harja Jelekong has an important role in introducing and strengthening cultural understanding in West Java. Interactive multimedia-based learning media can be used as one of the solutions to convey cultural wealth in an interesting and easy-to-understand way for the younger generation who are more familiar with technology. This research aims to build an interactive multimedia-based West Java cultural learning media application called Berbudaya Jabar. Luther's method, namely the Multimedia Development Life Cycle (MDLC), is used in the development of West Java cultural learning media applications at Kompepar Giri Harja Jelekong. MDLC consists of the stages of concept, design, material collection, manufacturing, testing, and distribution. The implementation of MDLC is a strategic step to utilize technology in cultural preservation. The resulting application is expected to be an effective, interactive, and interesting educational toolfot the younger generation, so that it can increase appreciation for West Javanese culture and preserve cultural heritage for the next generation.cultural learning media application at Kompepar Giri Harja Jelekong.